PERAN GURU DALAM PEMBINAAN PRILAKU KEAGAMAAN PESERTA DIDIK - Kamsiyah (UNISAN JURNAL, 2024)
The motivation behind this study was to decide the job of PAI educators in encouraging the ethics of understudies at Mts Darul Huda lubuk Harjo . This study utilizes a subjective methodology. While the strategy utilized in this exploration is graphic examination technique. The information assortment strategy utilized is perception, interview and documentation procedures. This participatory perception method was done to notice the geological area as an area plan and ecological circumstances, the school's vision, mission, system and maxim as well as the state of HR Mts Darul Huda lubuk Harjo . In view of the aftereffects of the depiction that has been portrayed that 1. The job of Islamic strict training educators in fostering the ethics of understudies plays had a functioning impact in the school. This should be visible from the direction done by Islamic strict schooling instructors, in particular the instructor goes about as an instructor, the educator as an instructor and the instructor as a good example. Creating projects and plans for creating understudy ethics is very ideal in completing understudy moral turn of events, yet PAI educators actually don't have a clue about their understudies either exclusively or in gatherings. 2. The ethics of understudies imparted by PAI educators in Mts Darul Huda lubuk Harjo , to be specific: ethics towards educators and representatives, ethics towards individual companions, understudies' ethics towards the school climate, understudies' ethics towards school tasks and understudies' ethics towards the standards and guidelines school.